INFLUENCE OF PSYCHOLOGICAL VIOLENCE OF TEACHERS ON SCHOOL MOTIVATION - Mkrtumyan, L. U. (Modern Psychology, 2019)
The article discusses the manifestations of psychological violence, as one of the factors violating the psychological safety of the educational environment, as well as their relationship with the educational motivation of students. The emotional reactions of students to the manifestations of psychological violence and their relationship with the level and types of educational motivation are revealed.